Interindustry Estimation of General Price-Level Impact on Financial Information: A Comment. - Basu, S.; Hanna, J. R. (The Accounting Review, 1978)
The article presents a comment by the authors on interindustry estimation of general price-level (GPL) impact on financial information. The January, 1973 issue of "The Accounting Review," contains an article by Russell Petersen that examined the impact of GPL adjustments on corporate financial statements. This comment is concerned with two specific shortcomings in the Petersen paper. First, it shows that his methodology for evaluating the impact of GPL restatements contains a fundamental error, which prevents an accurate assessment of the magnitude of "displacement" of certain of the financial parameters studied. The effect of this "comparability error" is sufficiently severe that it would alter some of Petersen's conclusions regarding the displacement effect of GPL restatements. Second, it questions the propriety of some of Petersen's statistical results and related discussion. It is believed that comparability error discussed in this article is but one example of a problem that is likely to arise with increasing frequency if disclosure of GPL restated information is required in the future.